Abnormal TDP‐43 function impairs activity‐dependent BDNF secretion, synaptic plasticity, and cognitive behavior through altered Sortilin splicing - Tann, Jason Y (EMBO J, 2019)
Aberrant function of the RNA‐binding protein TDP‐43 has been causally linked to multiple neurodegenerative diseases. Due to its large number of targets, the mechanisms through which TDP‐43 malfunction cause disease are unclear. Here, we report that knockdown, aggregation, or disease‐associated mutation of TDP‐43 all impair intracellular sorting and activity‐dependent secretion of the neurotrophin brain‐derived neurotrophic factor (BDNF) through altered splicing of the trafficking receptor Sortilin. Adult mice lacking TDP‐43 specifically in hippocampal CA1 show memory impairment and synaptic plasticity defects that can be rescued by restoring Sortilin splicing or extracellular BDNF. Human neurons derived from patient iPSCs carrying mutated TDP‐43 also show altered Sortilin splicing and reduced levels of activity‐dependent BDNF secretion, which can be restored by correcting the mutation. We propose that major disease phenotypes caused by aberrant TDP‐43 activity may be explained by the abnormal function of a handful of critical proteins, such as BDNF.